Barriers to research engagement among in-service EFL teachers in Esmeraldas - Ecuador: An exploratory study: Barreras para la participación en la investigación entre docentes de EFL en servicio en Esmeraldas - Ecuador: Un estudio exploratorio - Guerrero, Solange E; Estrada Alarcon, Diana Xiomara (Boletín Científico Ideas y Voces, 2025)
This exploratory study examines the barriers that limit research engagement among in-service English as a Foreign Language (EFL) teachers in Esmeraldas, Ecuador. While many educators demonstrate a genuine interest in conducting research, systemic and contextual challenges—such as limited institutional support, inadequate preparation in academic writing, and time constraints—impede their participation. Data were collected through a cross-sectional survey using purposive and snowball sampling, with responses from 21 EFL teachers across diverse educational settings. The findings reveal that, although structural obstacles persist, most participants do not perceive research as an exclusive domain for experts. This suggests a shift toward a more inclusive understanding of teacher inquiry. The study highlights the importance of targeted professional development and institutional reform to support a sustainable research culture within the EFL teaching community.